Formyl peptide receptor-2 is decreased in foetal growth restriction and contributes to placental dysfunction. (20th December 2017) - Lappas, Martha; McCracken, Sharon; McKelvey, Kelly; Lim, Ratana; James, Joanna; Roberts, Claire T; Fournier, Thierry; Alfaidy, Nadia; Powell, Katie L; Borg, Anthony J; Morris, Jonathan M; Leaw, Bryan; et al.
Abstract: STUDY QUESTION: What is the association between placental formyl peptide receptor 2 (FPR2) and trophoblast and endothelial functions in pregnancies affected by foetal growth restriction (FGR)? SUMMARY ANSWER: Reduced FPR2 placental expression in idiopathic FGR results in significantly altered trophoblast differentiation and endothelial function in vitro . WHAT IS KNOWN ALREADY: FGR is associated with placental insufficiency, where defective trophoblast and endothelial functions contribute to reduced feto-placental growth. STUDY DESIGN, SIZE, DURATION: The expression of FPR2 in placental tissues from human pregnancies complicated with FGR was compared to that in gestation-matched uncomplicated control pregnancies ( n = 25 from each group). Fpr2 expression was also determined in placental tissues obtained from a murine model of FGR ( n = 4). The functional role of FPR2 in primary trophoblasts and endothelial cells in vitro was assessed in diverse assays in a time-dependent manner. PARTICIPANTS/MATERIALS, SETTING, METHODS: Placentae from third-trimester pregnancies complicated by idiopathic FGR ( n = 25) and those from gestation-matched pregnancies with appropriately grown infants as controls ( n = 25) were collected at gestation 27–40 weeks. Placental tissues were also collected from a spontaneous CBA/CaH × DBA/2 J murine model of FGR. Placental FPR2/Fpr2 mRNA expression was determined by real-time PCR, while protein expression was examined by immunoblotting and immunohistochemistry. siRNA transfection was used to silence FPR2 expression in primary trophoblasts and in human umbilical vein endothelial cells (HUVEC), and the quantitation of cytokines, chemokines and apoptosis was performed following a cDNA array analyses. Functional effects of trophoblast differentiation were measured using HCGB /β-hCG and syncytin-2 expression as well as markers of apoptosis, tumour protein 53 ( TP53 ), caspase 8, B cell lymphoma 2 ( BCL2 ) and BCL associated X ( BAX ). Endothelial function was assessed by proliferation, network formation and permeability assays. MAIN RESULTS AND THE ROLE OF CHANCE: Placental FPR2 /Fpr2 expression was significantly decreased in FGR placentae ( n = 25, P < 0.05) as well as in murine FGR placentae compared to controls ( n = 4, P < 0.05). FPR2 siRNA (siFPR2) in term trophoblasts significantly increased differentiation markers, HCGB and syncytin-2 ; cytokines, interleukin (IL)-6, CXCL8 ; and apoptotic markers, TP53, caspase 8 and BAX, but significantly reduced the expression of the chemokines CXCL12 and its receptors CXCR4 and CXCR7 ; CXCL16 and its receptor, CXCR6 ; and cytokine, IL-10, compared with control siRNA (siCONT). Treatment of HUVECs with siFPR2 significantly reduced proliferation and endothelial tube formation, but significantly increased permeability of HUVECs. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Reduced expression of placental FPR2 /Fpr2 was observed in the third trimester at delivery after development of FGR, suggesting that FPR2 is associated with FGR pregnancies. However, there is a possibility that the decreased placental FPR2 observed in FGR may be a consequence rather than a cause of FGR, although our in vitro functional analyses using primary trophoblasts and endothelial cells suggest that FPR2 may have a direct or indirect regulatory role on trophoblast differentiation and endothelial function in FGR. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study linking placental FPR2 expression with changes in the trophoblast and endothelial functions that may explain the placental insufficiency observed in FGR. STUDY FUNDING/COMPETING INTERESTS: P.M. and P.R.E. received funding from the Australian Institute of Musculoskeletal Science, Western Health, St. Albans, Victoria 3021, Australia. M.L. is supported by a Career Development Fellowship from the National Health and Medical Research Council (NHMRC; Grant no. 1047025). Monash Health is supported by the Victorian Government's Operational Infrastructure Support Programme. The authors declare that there is no conflict of interest in publishing this work.